2004
DOI: 10.1200/jco.2004.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Shared Decision-Making Intervention Consisting of Trade-Offs and Individualized Treatment Information for BRCA1/2 Mutation Carriers

Abstract: We conclude that the SDMI improved decision making in unaffected BRCA1/2 mutation carriers. Supporting decision making in a systematic way using trade-offs is beneficial for these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 34 publications
4
103
2
Order By: Relevance
“…Several studies suggest using cancer genetic testing decision aids before testing to better inform patients about testing and to assure that they have more accurate risk perceptions. [115][116][117][118] An example of a decision aid used before cancer genetic testing is the computer program "Breast Cancer Risk and Genetic Testing," which is a CD-ROM-based program designed to educate women about breast cancer, heredity, and the benefits and limitations of genetic testing. Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest using cancer genetic testing decision aids before testing to better inform patients about testing and to assure that they have more accurate risk perceptions. [115][116][117][118] An example of a decision aid used before cancer genetic testing is the computer program "Breast Cancer Risk and Genetic Testing," which is a CD-ROM-based program designed to educate women about breast cancer, heredity, and the benefits and limitations of genetic testing. Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have examined shared decision-making (SDM) for a variety of illnesses and disabilities, including treatment decisions related to cancer 51 , mental illness 52 , and substance abuse. 53 Results have demonstrated that SDM leads to enhanced patient knowledge and patient satisfaction with treatment choices (Clinical Scenario 4).…”
Section: Shared Decision-making To Optimize Medica-tion Usementioning
confidence: 99%
“…Original study aims and detailed methods have been published elsewhere [21,22]. Questionnaires were sent at baseline, T1, that is after blood sampling to test for a BRCA1/2 mutation, at T2, 4 weeks after blood sampling, at T3, 2 weeks after a positive test result and at T4, 3 months after a positive test result.…”
Section: Methodsmentioning
confidence: 99%
“…Half of the women received a video and brochure [21], dealing with the decision between prophylactic surgery or screening for breast/ovarian cancer, 2 weeks after the blood sample, together with a follow-up questionnaire to evaluate this information. The outcome measures have been decribed in full detail [21,22]. A brief summary is given below.…”
Section: Methodsmentioning
confidence: 99%